2012
DOI: 10.1080/01490419.2012.718696
|View full text |Cite
|
Sign up to set email alerts
|

Global Surface Geostrophic Ocean Currents Derived from Satellite Altimetry and GOCE Geoid

Abstract: The surface geostrophic currents (SGC) can be derived via the principle of geostrophy from the dynamic height of the ocean, or the deviation of the true, variable sea surface height with respect to the Earth's static geoid, both of which can be measured by geodetic means. Here we calculate the Mean Dynamic Topography (MDT) by subtracting the geoid height determined by the GOCE satellite mission from the Mean Sea Surface Topography (MSST) derived from multi-satellite ocean altimetry (T/P, Jason 1/2, ERS-1/2, GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…The velocity map (cm/s) and the direction map for the annual mean climatology are presented in Fig. 1c, d. The results are in accordance with previous studies of the mean SGC (SÁ NCHEZ-REALES et al 2012;KNUDSEN et al 2011). The estimated velocities, Fig.…”
Section: Climatology Of Surface Geostrophic Currentssupporting
confidence: 78%
See 3 more Smart Citations
“…The velocity map (cm/s) and the direction map for the annual mean climatology are presented in Fig. 1c, d. The results are in accordance with previous studies of the mean SGC (SÁ NCHEZ-REALES et al 2012;KNUDSEN et al 2011). The estimated velocities, Fig.…”
Section: Climatology Of Surface Geostrophic Currentssupporting
confidence: 78%
“…This corresponds to a potential resolving power of approximately 86 km for the geoid. SÁ NCHEZ-REALES et al (2012) showed that, because of the nature of the GOCE, this resolution is sufficient to resolve the mean geostrophic flow for middle-to-high latitudes, but not for the equator, which remains a noisy band for which some filtering is needed (described in the Sect. 5).…”
Section: Geoidmentioning
confidence: 99%
See 2 more Smart Citations
“…That is because the GRACE TVG data quantify large-scale mass redistributions referenced to the time-mean static geoid, in our case the time-mean "climatology" field. To study the latter would call for the determination of the ocean dynamic topography which in turn entails the ocean surface topography relative to the static geoid (for example from satellite altimetry observations) (e.g., Sánchez-Reales et al 2012;Feng et al 2013), work that is outside the scope of the present study.…”
Section: Introductionmentioning
confidence: 99%